The effects of the Video Assistant Referee system (VAR) on the playing time, technical-tactical and physical performance in elite soccer - Errekagorri, I.; Castellano, J.; Echeazarra, I.; Lago-Peñas, C. (International Journal of Performance Analysis in Sport, 2020)
The main purpose of the present study was to assess if the intervention of the Video Assistant Referee (VAR) had effects in the playing time and in the technical-tactical and physical performances of the teams in the Spanish LaLiga during 2018-19 season. A total of 375 matches were grouped according the number of VAR interventions: none (VAR0), one (VAR1) and two or three (VAR2). The variables recorded were: total (TPT) and effective (EPT) playing time, passes, dribbles, crosses, shots, goals, corners, fouls, width, length, height, distance from the goalkeeper to their defence, and total (TD) and above 21 km/h distance covered. The results were: I) there was a slight increase in the TPT in VAR2 compared to VAR1 and VAR0 (99.1 vs. 96.0 vs. 95.1, respectively); II) there was a decrease in the EPT between VAR0 and VAR1 (52.5 vs. 51.5); III) there was an increase in the number of goals (1.2 vs. 1.5 vs. 1.7, in VAR0, VAR1 and VAR2); and, IV) there was a slight decrease in the TD (108,916 vs. 107,916 vs. 106,977, in VAR0, VAR1 and VAR2). In conclusion, the findings of the study suggest that the VAR hardly changes the game in elite soccer.